Assessment on transient sound radiation of a vibrating steel bridge due to traffic loading. (3rd February 2015) - Zhang, He; Xie, Xu; Jiang, Jiqing; Yamashita, Mikio
Abstract: Structure-borne noise induced by vehicle–bridge coupling vibration is harmful to human health and living environment. Investigating the sound pressure level and the radiation mechanism of structure-borne noise is of great significance for the assessment of environmental noise pollution and noise control. In this paper, the transient noise induced by vehicle–bridge coupling vibration is investigated by employing the hybrid finite element method (FEM) and boundary element method (BEM). The effect of local vibration of the bridge deck is taken into account and the sound responses of the structure-borne noise in time domain is obtained. The precision of the proposed method is validated by comparing numerical results to the on-site measurements of a steel girder-plate bridge in service. It implies that the sound pressure level and its distribution in both time and frequency domains may be predicted by the hybrid approach of FEM–BEM with satisfactory accuracy. Numerical results indicate that the vibrating steel bridge radiates high-level noise because of its extreme flexibility and large surface area for sound radiation. The impact effects of the vehicle on the sound pressure when leaving the bridge are observed. The shape of the contour lines in the area around the bridge deck could be explained by the mode shapes of the bridge. The moving speed of the vehicle only affects the sound pressure components with frequencies lower than 10 Hz.